Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
I
4 (x+1) = 3x+4
4x+4=3x+4
4x-3x=4-4
x=0
II
3(x-2) = 3x+6
3x-6=3x+6
3x-3x=6+6
0=12 sprzeczne
III
0,5 (x+2) -2 = 0,5x - 1
0,5x + 1 -2 = 0,5x - 1
0,5x- 0,5x = -1+2-1
0 = 0 tożsamościowe
[tex]4(x + 1) = 3x + 4 \\ 4x + 4 = 3x + 4 \\ 4x - 3x = 4 - 4 \\ x = 0[/tex]
[tex]3(x - 2) = 3x + 6 \\ 3x - 6 = 3x + 6 \\ 3x - 3x = 6 + 6 \\ 0 = 12[/tex]
SPRZECZNE
[tex]0.5(x + 2) - 2 = \frac{1}{2} x - 1 \\ 0.5x + 1 - 2 = 0.5 x - 1 \\ 0.5x - 0.5x = - 1 - 1 + 2 \\ 0 = 0[/tex]
TOŻSAMOŚCIOWE